ANALISIS PENGARUH EARNINGS MANAGEMENT TERHADAP PERUSAHAAN YANG MELAKUKAN PUBLIC OFFERING - Putri, Ekka Aminanti (Jurnal Akuntansi AKUNESA, 2013)
This paper examines the existance of earnings management of the IPO companies. Earnings management is affected when a company would conduct its first stock sale. Earnings management is a manager act who the form of intervene in the preparation offinancial statements with improving corporate profits. Goal of earnings management is toincrease the company's capital, to attract the attention ofinvestors.Companies that want to get more funding, the company can sell its shares to the public through the stock market. A manager in earnings management would prefer to use accrual transactions because this policy is more difficult to detect than the method of accounting. Accruall transaction is a transaction that does not affect the cash-out and cash in. The use of discretionary accrual sproven to be the managers for manipulating earnings because it is more difficult to detect by the investor. Keywords: Earnings Management, Initial Public Offering, Discretionary accruals.